Factors Affecting Implementation of Reporting Online Hospital Information Systems Second District Kediri - Ikke Winar Rachmawaty; Yuly Peristiowati; Novita Ana Anggraini (Journal for Quality in Public Health, 2020)
The need for data and information is currently growing very rapidly both in quantity and quality. With the enactment of Law Number 14 Year 2008 regarding Openness of Public Information (KIP), the availability of data and information is needed by the public. The data and information every year changes with the times, including the Hospital Information System (SIRS). The purpose of this study was to analyze the Factors Influencing the Implementation of Online SIRS in Hospitals in the District of Kediri. The design of this study was an observational quantitative study with a cross section approach with the focus of the research directed to be analyzing the Factors Influencing the Implementation of Online SIRS in Hospitals in the District of Kediri with a sample of 166 respondents taken with the Simple Random Sampling technique. The findings found that the majority of respondents had moderate motivation as many as 91 respondents (54.8%). Most respondents have knowledge in the medium category of 112 respondents (67.4%). Most respondents had a high category reward of 93 respondents (56.1%). Most respondents had a discrepancy with the sanctions provided by 88 respondents (56.3%). Most respondents lacked in conducting SIRS Online reports as many as 141 respondents (85.3%). The results of the study using the Logistic Regression Test showed that the most influential variable with a p-value of 0.006 <0.05 then H0 was rejected and H1 was accepted so it was concluded that there was a significant effect on the motivation of officers on the implementation of SIRS online at Hospitals in Kediri Regency . The effectiveness of implementing SIRS Online in hospitals can be influenced by the motivation of officers in implementing SIRS Online, the knowledge of officers in carrying out SIRS Online, rewards and sanctions received by officers. However, to be more effective in order to increase the motivation of officers to be willing to do SIRS Online reporting routinely and correctly.